A Small State with Growing Influence: Balancing Azerbaijan in Global Energy Policy - Suren Tadevosyan (Journal of Political Science: Bulletin of Yerevan University)
Azerbaijan holds a pivotal position in the global energy landscape due to its substantial hydrocarbon resources and strategic location between Europe and Asia. This study examines Azerbaijan’s role as a key energy supplier within the context of its relationships with the EU and Russia. Applying role theory as the analytical framework, the research explores how Azerbaijan conceptualizes, negotiates, and performs its energy diplomacy while balancing external pressures and internal objectives. The study addresses three core questions: how Azerbaijan’s identity as an energy supplier influences its foreign policy, how it aligns with the EU’s energy diversification and sustainability goals, and how it mitigates role conflicts with Russia while preserving its sovereignty. The research employs qualitative methods, analyzing secondary data and policy documents to assess Azerbaijan’s strategic approaches. The findings illustrate Azerbaijan’s ability to assert agency within asymmetrical power dynamics, reinforcing its energy role with the EU through infrastructure projects like the Southern Gas Corridor, while managing role conflicts with Russia through economic cooperation and pragmatic engagement. This analysis highlights Azerbaijan’s adaptability and strategic positioning, contributing to the broader discourse on small-state agency and the geopolitics of energy diplomacy.